Differential Mechanisms of Myocardial Conduction Slowing by Adipose Tissue‐Derived Stromal Cells Derived from Different Species. (January 2017) - ten Sande, Judith N.; Smit, Nicoline W.; Parvizi, Mojtaba; van Amersfoorth, Shirley C.M.; Plantinga, Josée A.; van Dessel, Pascal F.H.M.; de Bakker, Jacques M.T.; Harmsen, Marco C.; Coronel, Ruben
Abstract: Stem cell therapy is a promising therapeutic option to treat patients after myocardial infarction. However, the intramyocardial administration of large amounts of stem cells might generate a proarrhythmic substrate. Proarrhythmic effects can be explained by electrotonic and/or paracrine mechanisms. The narrow therapeutic time window for cell therapy and the presence of comorbidities limit the application of autologous cell therapy. The use of allogeneic or xenogeneic stem cells is a potential alternative to autologous cells, but differences in the proarrhythmic effects of adipose‐derived stromal cells (ADSCs) across species are unknown. Using microelectrode arrays and microelectrode recordings, we obtained local unipolar electrograms and action potentials from monolayers of neonatal rat ventricular myocytes (NRVMs) that were cocultured with rat, human, or pig ADSCs (rADSCs, hADSCs, pADSCs, respectively). Monolayers of NRVMs were cultured in the respective conditioned medium to investigate paracrine effects. We observed significant conduction slowing in all cardiomyocyte cultures containing ADSCs, independent of species used ( p < .01). All cocultures were depolarized compared with controls ( p < .01). Only conditioned medium taken from cocultures with pADSCs and applied to NRVM monolayers demonstrated similar electrophysiological changes as the corresponding cocultures. We have shown that independent of species used, ADSCs cause conduction slowing in monolayers of NRVMs. In addition, pADSCs exert conduction slowing mainly by a paracrine effect, whereas the influence on conduction by hADSCs and rADSCs is preferentially by electrotonic interaction. Stem Cells Translational Medicine 2017;6:22–30